2018
DOI: 10.1002/2017jd027080
|View full text |Cite
|
Sign up to set email alerts
|

Convectively Driven Tropopause‐Level Cooling and Its Influences on Stratospheric Moisture

Abstract: Characteristics of the tropopause‐level cooling associated with tropical deep convection are examined using CloudSat radar and Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) GPS radio occultation measurements. Extreme deep convection is sampled based on the cloud top height (>17 km) from CloudSat, and colocated temperature profiles from COSMIC are composited around the deep convection. Response of moisture to the tropopause‐level cooling is also examined in the upper tropospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 60 publications
6
47
0
Order By: Relevance
“…to the convective heating (Kim et al, 2018). As mentioned above, the response forces Rossby and Kelvin waves that effectively extend the dynamical influence of convection to the east.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 96%
See 3 more Smart Citations
“…to the convective heating (Kim et al, 2018). As mentioned above, the response forces Rossby and Kelvin waves that effectively extend the dynamical influence of convection to the east.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 96%
“…The wind vectors indicate the location of a pair of high pressure systems, one located just west of 180° longitude, north of the equator, and one over Australia south of the equator. These two systems are a result of the Matsuno‐Gill response to the convective heating (Kim et al, ). As mentioned above, the response forces Rossby and Kelvin waves that effectively extend the dynamical influence of convection to the east.…”
Section: Dynamics Of the Tropical Ttlmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the contribution of the vertical eddy flux is usually considered small in previous studies, a few studies have suggested its importance in determining the tropical tropopause temperature (e.g., Abalos et al, 2013;;Holloway & Neelin, 2007;Kim et al, 2018;Yoshida & Yamazaki, 2010). For example, Yoshida and Yamazaki (2010) performed numerical model experiments by modifying the tropical sea surface temperature and found the convergence of the vertical eddy heat flux critical in setting up the tropical tropopause temperature response.…”
Section: 1029/2019jd031552mentioning
confidence: 99%